Democracy, capitalism and racism: Latino labour and US capitalism. (1st January 2011) - Sy, Aida; Tinker, Tony
Since the US voters elected Barack Obama in 2008 – the first African American President of the United States of America – we witness continual attacks on this first black president. The attacks by the Tea Party have been widely broadcasted by those parts of the US media most sympathetic to their concerns. The Tea Party has also attacked Nancy Pelosi – the first woman Speaker of the House; the President's Healthcare Reform (initially planned to provide healthcare for 50 millions of Americans); the minimum wage and many other social protections for the middle class. Their other attacks were directed against the Latino labour.